Keamanan Data dengan Algoritma AES 128-Bit dan Bcrypt di PT. Anugrah Lancar Sukses - Rohadi Dwi Junianto; Yuni Wibawanti; Muhammad Akrom (Jurnal Teknologi Terpadu, 2026)
This study aims to design and implement a data security system based on the 128-bit Advanced Encryption Standard (AES) algorithm integrated with BCrypt authentication at PT. Anugrah Lancar Sukses. The research is motivated by the company’s practice of distributing internal documents without encryption, which increases the risk of data leakage and misuse. The system was developed using the Waterfall method, comprising requirements analysis, system design, implementation, and testing. The application was implemented as a desktop-based system featuring file encryption and decryption, user authentication, and role-based access control. System evaluation was conducted using Black-Box testing and cryptographic algorithm testing. The results indicate that all core system features functioned correctly with a 100% success rate. AES 128-bit encryption and decryption processes were completed efficiently, with an average processing time of less than one second for various file types, while maintaining data integrity after decryption. In addition, the BCrypt algorithm successfully secured user credentials by generating unique password hashes. These results demonstrate that the proposed system is effective in strengthening internal data protection and supporting information security practices within the organization.